Atypical erythema annulare centrifugum in a child with celiac disease. Issue 7 (21st July 2021) - Votto, Martina; De Filippo, Maria; Licari, Amelia; Caimmi, Silvia; Marseglia, Gian Luigi; Davidovich, Shay; Slawatyniec, Iga; Fraticelli, Sara; Barruscotti, Stefania; Brazzelli, Valeria
Abstract: Herpetiformis dermatitis is the best characterized extraintestinal manifestation of celiac disease (CD). However, other chronic heterogeneous skin lesions have been associated with CD and should be considered in the differential diagnosis. Abstract : Herpetiformis dermatitis is the best characterized extraintestinal manifestation of celiac disease (CD). However, other chronic heterogeneous skin lesions have been associated with CD and should be considered in the differential diagnosis.